Microalga (dunaliella salina): produção de carotenoides aplicados à nutrição de poedeiras - Fernandes, Raimunda Thyciana Vasconcelos (Universidade Federal Rural do Semi-Árido, 2017)
Considering that microalgae contain a wide variety of chemical and bioactive components that can be used in animal and human feeding, two experiments were performed. The first experiment aimed to evaluate the growth of the Dunaliella salina microalgae in two culture media, measuring its growth curve and productivity and its nutritional value. For the use of Conway mixotrophic and saline autotrophic culture media for 14 days. D. salina in Conway medium had an earlier exponential phase, with DCM (23,500 cells/mL), higher productivity and growth rate (p<0.05) than saline medium (18,200 cells/mL), although the cell diameter of D. salina was higher (p<0.05) in saline medium (25.5 μm ± 2.65) than in Conway medium (21.25 μm ± 1.26). The biomass of D. salina in Conway obtained higher values (P <0.05) of protein (60.43%), nitrogen (9.67 mg/g), chlorophyll a (60.60 mg/L), while medium saline provided higher values of lipids (6.93%), sugars (8.09%), gross energy (3955 kcal/kg), phosphorus (8.40 mg/g), potassium (128.66 mg/g), magnesium , Total extracellular polyphenols (81.00 mg/100 g), anthocyanins (30 mg/kg), zinc (8.23 mg/g), total carotenoids (34.73 mg/L), vitamin C 87mg/100g) and yellow flavonoids (45.30mg/100g). The use of the saline medium for the D. salina microalgae, although presenting lower rates of growth and productivity, resulted in a viable alternative to the Conway mixotrophic medium, because it allowed the biomass to obtain nutritional value similar to the commercial medium, and, with larger levels of antioxidants. For the second experiment, the objective was to evaluate the production, egg quality and intestinal morphometry of laying hens fed with the D. salina microalgae. A total of 120 laying hens were fed for 84 days, divided into three periods (28 days each), with five levels of inclusion of D. salina biomass (0, 0.25, 0.50, 0.75 and 1%). The productive performance of the chickens, the physical-chemical quality of the eggs, the morphometric alterations of the small intestine and liver were determined. The inclusion levels of the microalgae D. salina biomass had a linear effect on the performance (egg weight, egg mass, feed conversion), qualitative parameters (yolk weight, yolk index), and physicochemical parameters of eggs (total carotenoids, TBARS, and yolk color), as well as increasing the villi lengths and the villus/crypt ratio of the duodenum and ileum segments, as well as the metabolization of carotenoids in the liver. The inclusion of biomass of D. salina marine microalgae in experimental rations for laying hens improved the performance, the intestinal health of the birds and the physico-chemical quality of the eggs, besides conferring a higher carotenoid content, coloring the yolks and protecting them from oxidation lipid
Keywords: Antioxidantes; Biomassa; Compostos bioativos; Gema; Pigmentação; Antioxidants; Biomass; Bioactive compounds; Egg yolk; Pigmentation; CIENCIAS AGRARIAS::MEDICINA VETERINARIA